2012
DOI: 10.1016/j.cmet.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Is Required for AMPK Activation and the Beneficial Effects of Resveratrol on Mitochondrial Function

Abstract: SUMMARY Resveratrol induces mitochondrial biogenesis and protects against metabolic decline but whether SIRT1 mediates these benefits is the subject of debate. To circumvent the developmental defects of germ-line SIRT1 knockouts, we have developed the first inducible system that permits whole-body deletion of SIRT1 in adult mice. Mice treated with a moderate dose of resveratrol showed increased mitochondrial biogenesis and function, AMPK activation and increased NAD+ levels in skeletal muscle, whereas SIRT1 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
1,151
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,338 publications
(1,200 citation statements)
references
References 102 publications
35
1,151
0
14
Order By: Relevance
“…Several authors have shown deficits in mitochondrial function in the spinal cord and muscles of both human patients [64] and animal models of ALS [65][66][67]. Resveratrol improves mitochondrial function and induces biogenesis, although there is some controversy about whether this effect is mediated by AMPK activation [18] or by Sirt1 [16,68]. Since both Sirt1 and AMPK were found over-activated in SOD1 G93A animals treated with resveratrol, we performed a detailed analysis on mitochondria.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Several authors have shown deficits in mitochondrial function in the spinal cord and muscles of both human patients [64] and animal models of ALS [65][66][67]. Resveratrol improves mitochondrial function and induces biogenesis, although there is some controversy about whether this effect is mediated by AMPK activation [18] or by Sirt1 [16,68]. Since both Sirt1 and AMPK were found over-activated in SOD1 G93A animals treated with resveratrol, we performed a detailed analysis on mitochondria.…”
Section: Discussionmentioning
confidence: 98%
“…Sirt1 is a NAD + -dependent deacetylase that plays an important role regulating cell metabolism and has recently been postulated as a neuroprotective element in several neurodegenerative disorders [13]. Sirt1 induces protective effects since it is upstream of multiple effectors that participate in several cell processes, such as inflammation [43], autophagy [45] and mitochondrial function [16,46], all of them related to ALS physiopathology [5,56]. In the present work, we found that Sirt1 was overexpressed in spinal MNs of SOD1 G93A mice after resveratrol administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations